The Impact of 9/11 on Religion and Philosophy - Morgan, M. author. aut Link
XXI, 294 p.
Keywords: The Impact of 9-11 on Religion and Philosophy is the sixth volume of the six-volume series The Day that Changed Everything? edited by Matthew J. Morgan. This volume features a foreword by John Esposito and contributors include Jean Bethke Elshtain, Philip Yancey, John Milbank, Ada Maria Isasi-Diaz, John Cobb and Martin Cook.